Analisis Volume Produksi Berdasarkan Biaya Bahan Baku Dan Biaya Tenaga Kerja Langsung: (Studi Kasus Pada Pusaka Jaya Collection Tasikmalaya) - Ade Ima Nurwahidah (CV. Ulil Albab Corp, 2022)
This study aims to find out the simultaneous and partial effect of raw material costs and direct labor costs on production volume (Case Study on Pusaka Jaya Collection, Tasikmalaya Regency). The research method used is a causal relationship method with a quantitative approach. The sample used is the financial statements for 36 months. The data used is secondary data. The analytical tool used in this study is multiple regression using SPSS 25. The results showed that the cost of raw materials and direct labor costs had a significant effect on production volume simultaneously. Partially the cost of raw materials has a significant effect on the volume of production. Partially direct labor costs affect the volume of production.